2020
DOI: 10.2139/ssrn.3609586
|View full text |Cite
|
Sign up to set email alerts
|

Risk Preferences at the Time of COVID-19: An Experiment with Professional Traders and Students

Abstract: We study whether the COVID-19 pandemic has impacted risk preferences, comparing the results of experiments conducted before and during the outbreak. In each experiment, we elicit risk preferences from two sample groups: professional traders and undergraduate students. We find that, on average, risk preferences have remained constant for both pools of participants. Our results suggest that the increases in risk premia observed during the pandemic are not due to changes in risk appetite; rather, they are solely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 27 publications
1
35
0
Order By: Relevance
“…Consistently, the same panel data, which also included the SOEP general question for risk-taking, showed that women self-reported lower levels of risk-tolerance than men (Fan et al, 2020 ). While Drichoutis and Nayga ( 2020 ) and Chuang and Liu ( 2020 ) also found male participants to exhibit higher risk tolerance than their female participants, Angrisani et al ( 2020 ), on the other hand, did not find any effects associated with either gender or age.…”
Section: Background and Related Literaturementioning
confidence: 96%
See 1 more Smart Citation
“…Consistently, the same panel data, which also included the SOEP general question for risk-taking, showed that women self-reported lower levels of risk-tolerance than men (Fan et al, 2020 ). While Drichoutis and Nayga ( 2020 ) and Chuang and Liu ( 2020 ) also found male participants to exhibit higher risk tolerance than their female participants, Angrisani et al ( 2020 ), on the other hand, did not find any effects associated with either gender or age.…”
Section: Background and Related Literaturementioning
confidence: 96%
“…Similarly, Angrisani et al ( 2020 ) measure risk taking in a sample of 60 undergraduate students and 48 professional traders in London before and after the first wave of the pandemic in the UK using the Bomb Risk Elicitation Task (BRET) measure (Crosetto and Filippin, 2013 ), and find no statistically significant changes in the risk preferences in their samples. In seeming contrast, Ikeda et al ( 2020 ) measured risk tolerance in an online survey of 19,737 respondents in Japan between March and June 2020 using hypothetical questions, and found an increase in risk tolerance over time.…”
Section: Background and Related Literaturementioning
confidence: 99%
“…Risk preference and time preference choices play an important role in every person's life. These preferences influence economic agents' various activities such as saving, consumption and investment decisions (Angrisani et al 2020). Association of these preferences with situations that economic agents find themselves in, is equally crucial.…”
Section: Resultsmentioning
confidence: 99%
“…Association of these preferences with situations that economic agents find themselves in, is equally crucial. Angrisani et al (2020) emphasised the importance of assessing whether risk preferences are stable individual characteristics that are not affected by economic and social conditions among other factors. The notion that individuals are always rational when they make decisions has gradually lost its truthfulness.…”
Section: Resultsmentioning
confidence: 99%
“…These 3 outliers are against this result; removing them only strengthens it: the average number of boxes collected is 50 for traders and 40 for students 26. In a recent paper,Angrisani et al (2020) show that risk preferences using BRET are stable over time and in spite of a negative shock represented by the COVID-19 pandemic.…”
mentioning
confidence: 96%